2020
DOI: 10.1080/09638288.2020.1811406
|View full text |Cite
|
Sign up to set email alerts
|

How children and adolescents with juvenile idiopathic arthritis participate in their healthcare: health professionals’ views

Abstract: Background: The study explores how healthcare professionals view participation of children and adolescents with juvenile idiopathic arthritis, in healthcare encounters. Methods: This qualitative study includes focus groups of HCPs from different professions. The interviews were analysed with qualitative content analysis. Results: The theme "Creating an enabling arena" illuminates how HCPs face possibilities and challenges when enabling children to communicate and participate in clinical encounters. HCPs, paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…According to Fadyl et al, participants will relate to both' in-the-moment knowledge' and 'retrospective knowledge', during interviews [36]. In our earlier study, HCPs found children and parents to complement each other, and that older children could recall their health better [28]. Children and adolescents in this study described that they could remember health events well, but their parents could explain these in more detail.…”
Section: Methodological Considerationsmentioning
confidence: 57%
See 1 more Smart Citation
“…According to Fadyl et al, participants will relate to both' in-the-moment knowledge' and 'retrospective knowledge', during interviews [36]. In our earlier study, HCPs found children and parents to complement each other, and that older children could recall their health better [28]. Children and adolescents in this study described that they could remember health events well, but their parents could explain these in more detail.…”
Section: Methodological Considerationsmentioning
confidence: 57%
“…Likewise in a qualitative study by author date, HCPs could perceive that children and parents have different ways of communicating the child's health at healthcare encounters. Children were seen by HCPs to live in the moment, focusing on positive aspects, while the parents had a longer perspective and focused on the child's problems [28]. The concept Voice relates to these findings.…”
Section: Discussionmentioning
confidence: 99%
“…These families manage complex treatment regimens and regular visits with multiple subspecialists, including ophthalmology, psychology, and physical and occupational therapists, and usually require the long-term use of injectable and infusion therapies [ 14 ]. It is also known that children, parents, and clinicians have different views of disease and expectations of treatment outcomes, and it is important to enable children to actively communicate their views with their clinician [ 15 ].…”
Section: Introductionmentioning
confidence: 99%